Artificial Intelligence In The Automotive Industry 2.0 - V P, Selvakummar (Ushus Journal of Business Management, 2026)
Artificial Intelligence (AI) is changing the automotive industry across the world. It is helping the industry to work in new and improved ways. This change is considered one of the most important technological developments after the invention of the internal combustion engine. Today, AI is used in many stages of the automotive value chain. It supports vehicle design, improves manufacturing processes, and helps in quality control. AI also plays a major role in autonomous driving, smart vehicle connectivity, and customer support systems such as predictive maintenance and service recommendations. Technologies such as machine learning, deep learning, computer vision, IoT sensors, 5G networks, and edge computing are widely used in modern vehicles. These technologies help automotive companies increase accuracy, reduce human effort, and improve overall efficiency. AI systems also help vehicles understand their surroundings, make decisions, and react to road conditions in real time. This white paper explains the basic concepts of Artificial Intelligence used in the automotive sector. It discusses practical use cases, current challenges, and future opportunities. The paper is intended to support students, researchers, industry professionals, and policymakers who want to understand how AI can improve the future of mobility.